Preventing Multiple Sclerosis: The Pediatric Perspective - Hardy, Duriel; Chitnis, Tanuja; Waubant, Emmanuelle; Banwell, Brenda (Frontiers in Neurology, 2022)
Pediatric-onset multiple sclerosis (MS) is a predominantly relapsing-remitting neuroinflammatory disorder characterized by frequent relapses and high magnetic resonance imaging (MRI) lesion burden early in the disease course. Current treatment for pediatric MS relies on early initiation of disease-modifying therapies designed to prevent relapses and slow progression of disability. When considering the concept of MS prevention, one can conceptualize primary prevention (population- or at-risk population interventions that prevent the earliest facet of MS pathobiology and hence reduce disease incidence), or secondary prevention (prevention of disease consequence, such as reducing relapse frequency and lesion accrual, enhancing focal lesion repair, promoting CNS resilience against the more global facets of disease injury, and ultimately, preventing progression of neurological disability). Studying the pediatric MS population provides a unique opportunity to explore early-life exposures that contribute to the development of MS including perinatal and environmental risk determinants. Research is ongoing related to targeting these risk factors for potential MS primary prevention. Here we review these key risk factors, their proposed role in the pathogenesis of MS, and their potential implications for primary MS prevention.